2022
DOI: 10.3390/coatings12070940
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Interface Morphology of Thermal Barrier Coatings Based on Regulation of Residual Stress: A Finite Element Simulation Study

Abstract: Laser surface texture (LST) technology can be used to increase the adherence of thermal barrier coating (TBC). The primary research method is to conduct a large number of laser experiments to determine the optimal texture parameters. To minimize costs and enhance efficiency, in the current work, five types of circular pit textures were summarized; the plane strain model was established using the transient thermomechanical coupling finite element method; the residual stress field after spraying was used as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Wang et al found that the stress at the interface between the circular pit texture and coating increased with increasing diameter and depth over a certain range, and the stress could be reduced by changing the spacing of the textures. A suitable texture morphology could decrease the stress level within the coating and the lifetime of the coating was expected to be increased [57]. From other perspectives above, the effects of the USRP texture on the lubricating coatings were all positive, and it could be speculated that the cause of the negative effect of the W-D250 USRP texture was due to the negative interfacial stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that the stress at the interface between the circular pit texture and coating increased with increasing diameter and depth over a certain range, and the stress could be reduced by changing the spacing of the textures. A suitable texture morphology could decrease the stress level within the coating and the lifetime of the coating was expected to be increased [57]. From other perspectives above, the effects of the USRP texture on the lubricating coatings were all positive, and it could be speculated that the cause of the negative effect of the W-D250 USRP texture was due to the negative interfacial stresses.…”
Section: Discussionmentioning
confidence: 99%